2004
DOI: 10.1123/jsep.26.2.197
|View full text |Cite
|
Sign up to set email alerts
|

An Idiographic Analysis of Amotivation in Compulsory School Physical Education

Abstract: The purpose of this study was to provide an in-depth account of amotivation in compulsory school physical education by examining its major causes, the way it is displayed, and how it can be tackled. From an initial participant pool of 390 British schoolchildren ages 14 to 15 years, 21 of them (15 girls and 6 boys) were selected to participate in semi-structured interviews. They were categorized as being amotivated based on their responses to a questionnaire measuring motivation in physical education. Three mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
140
0
14

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(160 citation statements)
references
References 34 publications
6
140
0
14
Order By: Relevance
“…The work of Ntoumanis et al (2004) suggested that amotivated students require a physical education experience that satis es their psycho-social needs, as well as, enhances their level of enjoyment. Therefore, the purpose of this study is to examine the affect and needs satisfaction of amotivated students within the SEM.…”
Section: Sport Education Affect and Needs Satisfactionmentioning
confidence: 99%
See 3 more Smart Citations
“…The work of Ntoumanis et al (2004) suggested that amotivated students require a physical education experience that satis es their psycho-social needs, as well as, enhances their level of enjoyment. Therefore, the purpose of this study is to examine the affect and needs satisfaction of amotivated students within the SEM.…”
Section: Sport Education Affect and Needs Satisfactionmentioning
confidence: 99%
“…This popularity can be attributed to various mental, physical and affective consequences within activity-based settings (Vallerand, 2001). However, Ntoumanis, Pensgaard, Martin and Pipe (2004) suggested that there is "little research on the lack of motivation or amotivation " (p. 197). A reason for this lack of research could be due to the limited engagement and/or participation by amotivated students within physical education providing dif culty in attaining adequate data.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Desafortunadamente no todos los estudiantes tienen experiencias positivas en las clases de EF, lo que puede dar lugar a consecuencias desadaptativas como la desmotivación o unos niveles menores de participación (Brooks & Magnusson, 2006;Ntoumanis, Pensgaard, Martin & Pipe, 2004).…”
Section: Introductionunclassified